Translating Salafism into English: Anglo–Salafi Print Culture in Britain - Majothi, Azhar (2023)
Salafism is a contemporary Sunni Muslim reformist movement which is widely associated with Saudi Arabia although its non–Saudi adherents exist across the world. This thesis examines a previously understudied phenomenon related to the movement’s widespread visibility in the Anglosphere: Anglo–Salafi print culture. More specifically, its aim is to account for the widespread availability of English–language Salafi print material in contemporary Britain. Following 9/11, a number of academics, journalists, politicians and security experts misinterpreted this type of material as proof of Saudi Arabia’s petrodollar–fuelled “Wahhabi” agenda in Western countries. Given the heightened sensitivities surrounding Islamic extremism in the West, observers warned that Saudi state actors were funding religious intolerance in places like Britain partly through texts.